Development of teaching material based on plomp development model to support merdeka curriculum on global warming topic - Melati Alicia Firdaus; Mawardi Mawardi; Okta Suryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The COVID-19 pandemic has resulted in changes and impacts on education in Indonesia. One of the impacts is the emergence of learning loss, where students lose the competencies learned before and could be more optimal at completing learning. The government is updating the curriculum to overcome the existing problems. Based on the Ministry of Education, Research, and Technology decision, the curriculum applied now is the Merdeka Curriculum. With curriculum changes, additional teaching tools are needed as references that will be used in the learning process for teachers and students. Teaching materials are one teaching tool that teachers can use in the classroom. This study aims to produce Teaching Materials to Support The Merdeka Curriculum Learning on Global Warming Caused by Human Activities Material in Phase E. The research method used is Educational Design Research (EDR) using the Plomp development model, which consists of three stages: (1) Preliminary Research, (2) Development or Prototyping Phase, and (3) Assessment Phase. Data collection is carried out using a validity questionnaire sheet that will be given to five validators consisting of three lecturers and two teachers. Two teachers and nine high school phase E students will receive a practicality questionnaire sheet. Data from the research results show that the validity test conducted by five validators obtained a valid category score with a validity value of 0.89. The results of the practicality test on students obtained a score of 93% with a very practical category, and the value of the practicality test on the chemistry teacher was 92% with a very practical category. Teaching Materials to Support the Merdeka Curriculum Learning on Global Warming Caused by Human Activities Material are included in the valid and practical categories.